Análise imunoistoquímica de proteínas relacionadas à autofagia (Atg7, p62, LC3A e p-mTOR) em cistos radiculares, cistos dentígeros e ceratocistos odontogênicos - Ferreira, Christany Rodrigues (2021)
In the context of odontogenic cysts, the radicular cyst (RC), the dentigerous cyst (DC) and the odontogenic keratocyst (OKC) stand out for being the most prevalent. In the pathogenesis of cystic lesions, studies have highlighted the participation of an intracellular catabolic mechanism involving several proteins, especially Atg7, LC3A, p62 and p-mTOR. Until now, little is known about the involvement of this intracellular degradation mechanism in the pathogenesis of odontogenic cysts. Thus, the present study aimed to analyze the immunoexpression of autophagy-related proteins (Atg7, p62, LC3A and p-mTOR) in RCs, DCs and OKCs. The sample consisted of 20 RCs, twenty DCs and 20 OKCs. Clinical data (gender, age and anatomical location of the lesions) were collected from biopsy requisition forms. In the morphological study, the pattern of the epithelial lining and the intensity of the inflammatory infiltrate in the RCs were evaluated. In the immunohistochemical study, under 400× magnification, the percentages of positive cells (nucleus and cytoplasm) for proteins in 10 microscopic fields of the epithelial lining were established, as well as the predominance of immunoreactivity in the epithelial layers. The data obtained were submitted to statistical analysis using the Mann-Whitney test (p < 0.05). A higher frequency of RCs with grade III inflammatory infiltrate (55.0%) and hyperplastic epithelial lining (60.0%) was observed. All RCs, DCs and OKCs revealed cytoplasmic expression of Atg7 and p62. Nuclear expression of Atg7 and p62 was found in all OKCs, as well as in most RCs (90.0% and 95.0%, respectively) and DCs (80.0% and 95.0%, respectively). For these proteins, there was a predominance of immunoreactivity in the basal/parabasal layer in OKCs and in all layers of the epithelium in RCs and DCs. Cytoplasmic expression of LC3A was identified in most RCs (70.0%), DCs (85.0%) and OKCs (65.0%). Nuclear expression of LC3A was observed in most RCs (70.0%) and DCs (70.0%), as well as in a smaller proportion of OKCs (35.0%). There was a predominance of immunoreactivity for LC3A in the parabasal/superficial layer of the epithelium in OKCs. On the other hand, RCs and DCs exhibited considerable variability in LC3A immunoreactivity in the epithelial layers. Cytoplasmic expression of p-mTOR was observed in all DCs and OKCs, as well as in 50.0% of RCs. Nuclear positivity for p-mTOR was identified more frequently in DCs (70.0%), followed by OKCs (55.0%) and RCs (25.0%). In all groups, there was a predominance of p-mTOR immunoreactivity in the superficial layer of the epithelium. Higher percentages of cytoplasmic positivity for Atg7 were identified in RCs and OKCs when compared to DCs, with a significant difference between the last two (p < 0.05). No significant differences were observed between groups for cytoplasmic expression of LC3A (p > 0.05). The highest median percentages of cytoplasmic positivity for p62 and p-mTOR were observed, respectively, in RCs (p < 0.05) and OKCs (p < 0.05). OKCs showed higher nuclear expression of Atg7 compared to RCs and DCs (p < 0.05). Furthermore, RCs and OKCs exhibited higher nuclear expression of p62 compared to DCs (p < 0.05). All groups showed low percentages of nuclear positivity for LC3A and p-mTOR. No significant differences were found in the expression of autophagy-related proteins according to the pattern of the epithelial lining and the intensity of the inflammatory infiltrate in the RCs (p > 0.05). The results of this study suggest the participation of autophagy in the pathogenesis of RCs, DCs and OKCs. Nevertheless, the immunoexpression of Atg7, LC3A, p62 and p-mTOR proteins may not be related to the histopathological characteristics of RCs. Furthermore, the nuclear translocation of Atg7 and p62 proteins may contribute to the more aggressive biological behavior of OKCs.